Leucocyte immunoglobulin-like receptor subfamily-B5 (LILRB5) genetic variation and statin-associated muscle symptoms: another piece in a puzzling puzzle - März, Winfried; Laufs, Ulrich (European heart journal, 2017)
Abstract